Improving Students’ Ability to Recognize the Concept of Numbers 1-10 through the Modification of the Bocce Game for Mentally Retarded Children while the Class VII In SLB Negeri 2 Padang - Wahedatul Wahedatul; Asep Ahmad Sopandi (EDUTEC : Journal of Education And Technology, 2019)
This study discusses the introduction of the concept of numbers 1-10 to a mentally disabled child. The aim is to prove that the effective bocce game is used to advance the skills of mentally disabled children in understanding the concepts of numbers 1-10. This research uses experimental research in the form of Single-Subject Research (SSR). The study was conducted with three baseline conditions (A1), intervention (B) and baseline (A2), then the data were processed using graphs. The results showed the baseline (A1) condition was observed five times; the ability of children in this condition experienced the same that is fixed at a percentage of 35%. Furthermore, in the intervention condition and the second baseline, the child's skills in increasing their acquisition value (32.5% -85%), in the intervention condition and (75.5% -87.5%) in the baseline (A2) condition. Thus, the proposed hypothesis is accepted with a tendency towards (+), a tendency for 20% overlapping variable stability data, meaning that through the game, Bocce Modification can advance the skills of mentally disabled children to understand the concept of numbers 1-10.